2020
DOI: 10.3390/jlpea10030029
|View full text |Cite
|
Sign up to set email alerts
|

Power Management Circuits for Low-Power RF Energy Harvesters

Abstract: The paper describes the design and implementation of power management circuits for RF energy harvesters suitable for integration in wireless sensor nodes. In particular, we report the power management circuits used to provide the voltage supply of an integrated temperature sensor with analog-to-digital converter. A DC-DC boost converter is used to transfer efficiently the energy harvested from a generic radio-frequency rectifier into a charge reservoir, whereas a linear regulator scales the voltage supply to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…28,91 However, from the various reviews, 1,23,[28][29][30][31][32][33][34] we state that RF-based EH remains the best solution for various application scenarios related to low-energy IoT devices. Eltresy et al, 92 Caselli et al, 93 and Lin et al 94 highlight the RF-based EH potentials for IoT-based environmental and healthcare monitoring applications. There are other approaches exploiting RF-based EH techniques and include opportunistic charging from nearby smartphones.…”
Section: Rf-based Eh-wptmentioning
confidence: 99%
“…28,91 However, from the various reviews, 1,23,[28][29][30][31][32][33][34] we state that RF-based EH remains the best solution for various application scenarios related to low-energy IoT devices. Eltresy et al, 92 Caselli et al, 93 and Lin et al 94 highlight the RF-based EH potentials for IoT-based environmental and healthcare monitoring applications. There are other approaches exploiting RF-based EH techniques and include opportunistic charging from nearby smartphones.…”
Section: Rf-based Eh-wptmentioning
confidence: 99%
“…An example for the AC to DC rectifier could be the electronics demonstrated in this paper [ 69 ]. A complete power management system suitable for the application is presented in this paper [ 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on a review of the past literature in this area [61 -63], we found that RF waves energy harvesting is the best solution in many scenarios when it comes to low-energy IoT devices. The works in [64,65] and [66] highlight the potential of using RF Energy Harvesters (RFEHs) to power IoT devices for environmental and healthcare monitoring. Other approaches for harvesting energy from RF signals include opportunistic charging from nearby smartphones [67], or the sharing of energy between different wireless systems close to each other [68].…”
Section: Rf Energy Harvestingmentioning
confidence: 99%